2011
DOI: 10.1002/hep.23952
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir disoproxil fumarate (TDF), emtricitabine/TDF, and entecavir in patients with decompensated chronic hepatitis B liver disease

Abstract: Data are limited on the safety and effectiveness of oral antivirals other than lamivudine and adefovir dipivoxil for treatment of chronic hepatitis B (CHB) in patients with decompensated liver disease. This Phase 2, double-blind study randomized 112 patients with CHB and decompensated liver disease to receive either tenofovir disoproxil fumarate (TDF; n = 45), emtricitabine (FTC)/TDF (fixed-dose combination; n = 45), or entecavir (ETV; n = 22). The primary endpoint was safety; more specifically, tolerability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
235
5
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(270 citation statements)
references
References 30 publications
19
235
5
11
Order By: Relevance
“…In a randomized, controlled study of 112 patients with mildly decompensated cirrhosis (average MELD score 11, CTP score 7), HBV DNA at week 48 was undetectable in 71% of tenofovir-treated patients, 88% treated with emtricitabine plus tenofovir (FTC/ TDF), and 73% treated with entecavir. 9 Hepatitis B e antigen seroconversion occurred significantly less frequently with entecavir, but this may have been influenced by inclusion of lamivudine-pretreated patients and switching to open-label FTC/TDF if viremia persisted at week 24.…”
Section: Decompensated Cirrhosismentioning
confidence: 98%
“…In a randomized, controlled study of 112 patients with mildly decompensated cirrhosis (average MELD score 11, CTP score 7), HBV DNA at week 48 was undetectable in 71% of tenofovir-treated patients, 88% treated with emtricitabine plus tenofovir (FTC/ TDF), and 73% treated with entecavir. 9 Hepatitis B e antigen seroconversion occurred significantly less frequently with entecavir, but this may have been influenced by inclusion of lamivudine-pretreated patients and switching to open-label FTC/TDF if viremia persisted at week 24.…”
Section: Decompensated Cirrhosismentioning
confidence: 98%
“…Another study by Liaw et al 2011 [15] showed similar results with reduction in CP and MELD scores under Tenofovir and Entecavir patients. Changes in CP score were observed in various studies after antiviral treatment for HBV, CP score mean reduction ≥2 was found in lamivudine in 39% of patients, adefovir in 27%, entecavir in (35-49%) and tenofovir in 26% [18,19,20,15,21] .…”
Section: Discussionmentioning
confidence: 68%
“…The current study showed that 91.2% of patients in both groups had undetectable serum HBV DNA at 12 months and there was no viral breakthrough in any patient of indicating similar efficacy of both drugs in suppressing HBV replication. amulticenter randomized study by Liaw et al 2011 [15] , showed that both drugs have similar virologic efficacy in patients with HBV decompensated cirrhosis, they found no difference in virologic efficacy. Also, Evangelos et al 2015 [5] reported better response rate as all patients had undetectable HBV DNA serum at end of treatment with Tenofovir and Entecavir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some also suggest vaccination in primary stages of development of kidney disease. [16][17][18][19][20] In a study, Sanadgol et al investigated levamisole as adjuvant for improvement of response to hepatitis B vaccination in hemodialysis patients and conclude that levamisole did not lead to significant increase in antibody titer in the second and 4 th month and only anti-HBV antibody level was significantly lower immediately after HBV vaccination when it was accompanied by levamisole administration. 21 According to published literature, it seems that there is no study conducted on effect of levamisole as adjuvant to improve response rate to hepatitis B vaccination in patients suffering from CKD in stage before starting hemodialysis.…”
Section: Acir/jarcmmentioning
confidence: 99%